FACTORS INFLUENCING THE ADOPTION OF INFORMATION COMMUNICATION TECHNOLOGY (ICT): IN SELECTED, RATED, HOTELS IN ADDIS ABABA, ETHIOPIA - Agegnehu, Menen; Lemi, Kenenisa; Mulatu, Firew (Journal of process management and new technologies, 2019)
Information communication technology has important impact in our day to day activities. ICT to be recognized it has to be diffused in the community to see and get its effects. Adoption of ICT has become a key enabler of technology readiness in many countries. The purpose of this study is to investigate factors influencing adoption of ICT in star rated hotels with focus on 3,4 and 5 star hotels in Addis Ababa. Thus, the study investigates how organizational, manager’s ICT knowledge, technology innovation and environmental factors influencing ICT adoption in management of hotels. The study used both primary and secondary data. Questionnaire was adopted from a similar study and passed reliability test. Descriptive, correlation and multiple linear regression was used to analyze the data. Finding revealed that Organizational related factors, Manger’s ICT knowledge, Technology innovation factors and Environmental factors were influenced the adoption of ICT in the hotel management. Technology innovation determines ICT adoption in hotel management to a great extent followed by Environmental factors, ICT knowledge of Owner’s/Managers and Organizational factor. It is recommended that the owners/mangers of the hotel needs to understand the benefit of adopting the ICT and make the technology easier to their customers and employees for sustainable ICT adoption.